Arctic researches and life among the Esquimaux [electronic resource] : being the narrative of an expedition in search of Sir John Franklin, in the years 1860, 1861 and 1862 - Hall, Charles Francis, 1821-1871 (New York : Harper, 1866)
Added t.p.: Hall's Arctic research expedition and life among the Esquimaux. Electronic reproduction. Mode of access: Internet. 44